Household migration decisions as survival strategy: the case of Burkina Faso - Adama Konseiga (Institute for the Study of Labor (IZA), 2005)
The paper examines the motivations behind the important migration from Burkina Faso to Côte d'Ivoire, the economic pole in the West African Economic and Monetary Union. The paper uses a detailed household survey dataset on migration, natural resource management, risk management and solidarity collected in 2000 and 2002 in Northeastern Burkina Faso. In addition to the household survey, two other village and institutional level surveys were conducted. The methodology emphasizes the linkage between economic theories and empirical evidence, using econometric tools that are robust to the selection bias. It enables to study the specificities of the seasonal migration and estimate migration incomes. The structural model of migration decision revealed the importance of migration as a mere survival strategy in the study regions confronted with severe scarcity of natural resources. Results supported that even under the pessimistic scenario where the direct benefits of the regional integration program would go exclusively to the polar economy, households in the Sahel may still benefit from an increased economic attractiveness of this destination. First, because it is seasonal, the increased migration will translate into higher liquidity that enables households to overcome credit and insurance market failures and invest in their main agropastoral activities. Second, an interesting finding is also the role of the unsecured livestock activity as impediment to migration of the pastoralist groups. The study recommended the development of policies that address security issues through well-functioning rural labor market institutions and enforceable rules regarding shepherd contracts. It is also important to enforce regional laws regarding the free movement of labor.
Keywords: C25; F15; F22; R23; J31; 330; international migration; Todaro model; new economics of labor migration; sample selection; income functions